Global, regional, and national burden of musculoskeletal disorders, 1990–2021: an analysis of the global burden of disease study 2021 and forecast to 2035 - Liu, Meizhi; Rong, Jian; An, Xiangzhen; Li, Yulei; Min, Yan; Yuan, Guomeng; Yang, Yan; Li, Mengjie (Frontiers in Public Health, 2025)
ObjectivesThis study aimed to assess the global, regional, and national burdens of musculoskeletal disorders (MSDs) since 1990. It also projected trends up to 2035 and explored potential improvements through frontier analysis.MethodsUsing data from the Global Burden of Disease 2021 study, MSDs in 204 countries and territories were analyzed. Age-standardized rates (ASRs) for prevalence (ASPR), incidence (ASIR), DALYs (ASDR), and mortality (ASMR) were calculated. Trends were evaluated through estimated annual percentage changes (EAPC). The Bayesian age-period-cohort (BAPC) model was employed for projections to 2035, and frontier analysis was used to assess the potential for reducing MSD burdens.ResultsIn 2021, 1.686 billion MSDs prevalent cases were recorded globally, representing a 95% increase since 1990. Although total cases and DALYs have increased, ASIR and ASMR showed declining trends, with global MSD-related mortality decreasing by 0.265% annually. By 2035, the number of MSD cases is projected to rise to 2.161 billion, along with corresponding increases in DALYs and mortality, although ASRs are expected to continue declining. Frontier analysis revealed significant gaps between current burdens and achievable benchmarks, particularly in high-SDI regions, while some low-SDI regions demonstrated effective management despite limited resources. A U-shaped relationship between SDI and MSDs burdens was observed, with middle-SDI regions generally performing better.ConclusionThe global burden of MSDs is projected to rise in absolute case numbers, underscoring the necessity for strategically targeted interventions to manage their impact effectively. Frontier analysis illuminates potential improvements, particularly in high-SDI countries, while projections indicate that enhanced access to healthcare and better resource distribution could alleviate the global MSDs burden. Addressing disparities and implementing tailored interventions are crucial for reducing MSDs-related disability and mortality.